New Zealand : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper assesses the impact of a disruption to capital inflows by examining past episodes of capital inflows in New Zealand and other countries. It also reviews the IMF's Global Economy Model (GEM), which is used to provide some estimates of the equilibrium relationship between New Zealand's real effective exchange rate and real commodity prices. The analysis also suggests that permanent changes in non-energy commodity prices can have a significant impact on New Zealand's equilibrium exchange rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet